2020
DOI: 10.3390/s20205846
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Health Stage Prediction Using Convolutional Neural Networks for Bearing Wear

Abstract: Early detection of faults in rotating machinery systems is crucial in preventing system failure, increasing safety, and reducing maintenance costs. Current methods of fault detection suffer from the lack of efficient feature extraction method, the need for designating a threshold producing minimal false alarm rates, and the need for expert domain knowledge, which is costly. In this paper, we propose a novel data-driven health division method based on convolutional neural networks using a graphical representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…The assumption is labeling a small portion of the run-to-failure dataset where the signals are clearly distinguishable into healthy and unhealthy when no labels for health stages are given. In the previous study [26], we found that the FPT is not sensitive to p ranging from 0.05 to 0.5. p = 0.05 is used in the experiments in Section 4. By the CNN-based binary regression model, the HS and the FPT of the jth bearing, T F P T j , can be determined.…”
Section: Loss Functions and Training Proceduresmentioning
confidence: 68%
See 4 more Smart Citations
“…The assumption is labeling a small portion of the run-to-failure dataset where the signals are clearly distinguishable into healthy and unhealthy when no labels for health stages are given. In the previous study [26], we found that the FPT is not sensitive to p ranging from 0.05 to 0.5. p = 0.05 is used in the experiments in Section 4. By the CNN-based binary regression model, the HS and the FPT of the jth bearing, T F P T j , can be determined.…”
Section: Loss Functions and Training Proceduresmentioning
confidence: 68%
“…Although unsupervised methods [25], such as auto-encoder, promise the extraction of efficient health indicators(HI); however, they possess a challenge assigning an appropriate threshold for determining FPT. Recently, the CNN-based HS division methods have been proposed, but they require an appropriate threshold to determine the FPT [24] or need to determine bandwidths, where there are significant differences between normal and faulty conditions [21,26]. Li et al [24] proposed a GAN-based RUL prediction approach that consists of two stages.…”
Section: Deep Learning and Adversarial Domain Adaptation For Rulmentioning
confidence: 99%
See 3 more Smart Citations